Wide-Band Nonlinear Chirp Transducers for Planar Acoustooptic Deflectors - Anemogiannis, Kimon; Russer, Peter; Weigel, Robert (IEEE MTT-S International Microwave Symposium Digest, 1989, 1989)
The design, fabrication, and performance characteristics of LiNbO/sub 3/-based wideband nonlinear interdigital chirp transducers are reported. A 54% bandwidth centered at 720 MHz has been obtained for a collinear deflector on a YX substrate. A 66% bandwidth at a midband frequency of 600 MHz has been designed for a Bragg deflector on a YZ substrate with electrodes tilted to satisfy the Bragg condition. Both transducers are down-chirp designs. The chirp waveform has been optimized using an accurate model of analysis. The transducers have been fabricated using 10:1 reduction projection printing and the liftoff technique. Good agreement has been found between theory and measurement. No severe bulk wave generation has been observed.<>
–empty–::1512001600,anemogiannis1989
Keywords: acousto-optical devices; integrated optics; lithium compounds; optical deflectors; ultrasonic transducers; 10:1 reduction projection printing; Frequency response; Surface acoustic waves